Job satisfaction and organizational citizenship behaviour of employees in companies in the Republic of Serbia - Đorđević Biljana (University of Novi Sad - Faculty of Economics, Subotica, 2021)
Organizational citizenship behaviour is a form of employees' behaviour where employees go beyond their formal duties required by job description. Despite the fact that this form of behaviour is not recognized or accepted by the reward system, employees are ready to put in an extra effort in order to achieve organizational goals. However, the readiness of employees to manifest this form of behaviour is not completely unconditional. Numerous empirical studies suggest that such behaviour can be encouraged by employees' job satisfaction, fulfilment of their psychological contract, perception of a high level of organizational justice in the company, support provided to them, etc. Having in mind the importance of this form of employees' behaviour, precisely from the point of view of employers, as well as the factors that influence it, this paper examines the impact of employees' job satisfaction on the level of their organizational citizenship behaviour on the example of the companies in Serbia. The paper starts with three hypotheses. The first and second hypotheses are that employees in companies in Serbia are satisfied with their jobs and that they demonstrate organizational citizenship behaviour. These assumptions were tested using the t-test. The third hypothesis is that employees' satisfaction with their job has a positive effect on their organizational citizenship behaviour. In order to test this hypothesis, methods of correlation and multiple regression analysis were used. The analysis is based on data obtained by primary research realized during 2019. In the research, 244 employees participated. The research showed that there is a positive relationship between respondents' job satisfaction and organizational citizenship behaviour, as well as the positive impact of job satisfaction on organizational citizenship behaviour of employees. This paper's contribution is twofold. First, it provides empirical data regarding the job satisfaction and organizational citizenship behaviour of employees in companies in Serbia. Second, it adds to the existing literature from this field by proposing strategies for increasing the employees' job satisfaction, which will lead to increasing the employees' willingness to manifest organizational citizenship behaviour.